Predicting the emergence of content words in L2 diary entries during study abroad over a year. (October 2019) - KAMIYA, Nobuhiro
Abstract: This case study examined a diary written by a Japanese senior high school student while he was studying abroad in the US for a year. His writings exhibited two types of texts throughout the year: code-mixed texts, in which a mixture of Japanese and English is used, and code-switched texts, in which only English is used, in a single sentence. The diary was examined to identify to what extent the emergence of content words under spontaneous written production ( n  = 1, 716) could be predicted by their word frequency, degree of cognate similarity, and word length while comparing the two types of texts. According to the results of multiple regressions, word frequency was found to be a significant predictor for both texts, indicative of its robust effects. The effects of the degree of cognate similarity appeared only for code-mixed texts. The effects of word length were, if any, limited. Furthermore, code-mixed texts were found to yield longer words with lower word frequencies and higher degrees of cognate similarity than code-switched texts. Considering that the results here may be influenced by the duration of study abroad, this study reconfirms the significance of tracking the micro-development of vocabulary for second language learners.